Middle Cerebellar Peduncle Cavernous Malformation (Cavernoma): Case Report - Sá, Liliana (2022)
Cavernous malformations are almost asymptomatic cerebral vascular malformations. In children, these low-blood flow lesions are the main causes of cerebral hemorrhage besides arteriovenous malformations. Cerebral cavernous malformations can radiologically and clinically mimic a tumor with bleed. Radiological studies (MRI) provide the diagnosis andhistopathological examination confirms it. We report a case of a 14-year-old male patient who presented with five days history of dizziness, imbalance, tinnitus, hearing loss and paresthesia of the face and tongue on the right. A magnetic resonance revealed a multi-cystic, right middle cerebellar peduncle mass, showing areas of hemorrhages with various stages of thrombus. Cerebral angiography ruled out an arteriovenous malformation. He underwent a surgery, with a complete removal, decision based on location and symptomatic presentation mode. Histopathology confirmed a cavernous malformation. The patient had no new neurological deficit and he had an uneventful postoperative recovery. Late follow-up magnetic resonance confirmed total removal of the lesion.